Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.jpcc.1c06778
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Gold Nanorods: A SAXS Study

Abstract: Using simultaneous, in situ optical spectroscopy and time-resolved, small-angle X-ray scattering (SAXS), we have directly monitored the seeded growth of nearly monodisperse gold nanorods using hydroquinone as the reductant. Growth of the rods is much slower than with the ascorbate ion, allowing the rate of growth along both the longitudinal and transverse directions to be independently determined. The thickness of the stabilizing CTAB layer (3.2 ± 0.3 nm) has also been extracted. We find that increasing the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 48 publications
(90 reference statements)
1
24
0
Order By: Relevance
“…Due to the complementary information from simultaneous SAXS/SANS, extracting the CTAB layer density this way is inherently more reliable than previous studies on this topic. [23,38,39] Nevertheless, more detailed measurements should be performed using this method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the complementary information from simultaneous SAXS/SANS, extracting the CTAB layer density this way is inherently more reliable than previous studies on this topic. [23,38,39] Nevertheless, more detailed measurements should be performed using this method.…”
Section: Resultsmentioning
confidence: 99%
“…UV–vis spectra of AuNR synthesized during the simultaneous SAXS/SANS experiment show similar quality to particles synthesized in a recently presented in‐situ study as indicated by the transversal surface plasmon resonance at around 550 nm. [ 2,23 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These multi-method time-resolved studies have been conducted in a variety of systems, although there are significant challenges in the interpretation. For instance, the growth of Au and Pt nanorods in an aqueous solution has been followed similarly, and one of the authors has reported results from UV–visible absorption spectroscopy, SAXS, and NEXAFS …”
Section: Introductionmentioning
confidence: 99%